Dampak Terorisme dan Peran Media Dalam Propaganda Islamofobia: Tinjauan Pustaka Sistematis - Muhammad Firdaus Syadzili (Universitas Palangka Raya, 2024)
Terrorist movements have often been heard, both in Indonesia and in other remote parts of the country. Several studies have discussed whether terrorism is included in the impact of globalization where the movement spreads rapidly along with globalization and becomes one form of transnational movement that eventually enters other countries and develops rapidly and immediately spreads ideas to existing countries. First, identify the article. Articles are taken from publications by various authors using the Scopus database. The next step is to enter the keyword